Frequency Domain Deep Learning with Non-Invasive Features for Intraoperative Hypotension Prediction - Moon, Jeong Hyeon; Lee, Garam; Lee, Seung Mi; Ryu, Jiho; Kim, Dokyoon; Sohn, Kyung Ah (IEEE Journal of Biomedical and Health Informatics, 2024)
Background: Intraoperative hypotension can lead to postoperative organ dysfunction. Previous studies primarily used invasive arterial pressure as the key biosignal for the detection of hypotension. However, these studies had limitations in incorporating different biosignal modalities and utilizing the periodic nature of biosignals. To address these limitations, we utilized frequency-domain information, which provides key insights that time-domain analysis cannot provide, as revealed by recent advances in deep learning. With the frequency-domain information, we propose a deep-learning approach that integrates multiple biosignal modalities. Methods: We used the discrete Fourier transform technique, to extract frequency information from biosignal data, which we then combined with the original time-domain data as input for our deep learning model. To improve the interpretability of our results, we incorporated recent interpretable modules for deep-learning models into our analysis. Results: We constructed 75 994 segments from the data of 3226 patients to predict hypotension during surgery. Our proposed frequency-domain deep-learning model outperformed conventional approaches that rely solely on time-domain information. Notably, our model achieved a greater increase in AUROC performance than the time-domain deep learning models when trained on non-invasive biosignal data only (AUROC 0.898 [95% CI: 0.885-0.91] vs. 0.853 [95% CI: 0.839-0.867]). Further analysis revealed that the 1.5-3.0 Hz frequency band played an important role in predicting hypotension events. Conclusion: Utilizing the frequency domain not only demonstrated high performance on invasive data but also showed significant performance improvement when applied to non-invasive data alone. Our proposed framework offers clinicians a novel perspective for predicting intraoperative hypotension.
Keywords: Biological system modeling; Biosignals; Deep learning; Features extraction; Fourier's analysis; Frequency domains; Hypotension; Hypotension detection; Aged; Deep Learning; Female; Fourier Analysis; Humans; Hypotension; Intraoperative Complications; Male; Middle Aged; Monitoring, Intraoperative; Signal Processing, Computer-Assisted; Deep learning; feature extraction; Fourier analysis; hypotension detection